Unforgettable - Von Ziegesar, Cecily (New York : Little, Brown, 2007)
Callie Vernon never really liked late-night girl talk or swapping cashmere sweaters with her younger, rosy-cheeked roomie, Jenny Humphrey. So when Jenny stole her longtime boyfriend, Easy Walsh, Callie didn't feel that guilty about turning right around and kissing him behind Jenny's back.
Ages 15 and up.
Keywords: Boarding schools -- Fiction; Teenage girls -- Fiction; Interpersonal relations -- Fiction; Wealth -- Fiction; Conduct of life -- Fiction; New York (State) -- Fiction